Hot Spot Peacekeeping1. Issue 1 (27th February 2015) - Powers, Matthew; Reeder, Bryce W.; Townsen, Ashly Adam
Abstract : One of the goals of peacekeeping operations is limiting the amount of violence that takes place during a civil war. However, peacekeeping forces cannot occupy every part of a country that is engulfed in a civil conflict. This raises the question as to where peacekeeping forces decide to go once they are deployed to a civil war‐torn country. In this article, we contribute to the burgeoning research that examines peacekeeping at the microlevel by attempting to determine whether peacekeeping operations go to those areas that are in most need of their help. Utilizing geocoded data from the UCDP GED and PKOLED projects, we use spatial analysis techniques to create kernel density estimates of civil war violence and peacekeeping operations at site‐specific locations. We then use these newly generated variables in a variety of regression models to determine whether the location of civil war battles influences the location of peacekeepers. The analysis confirms our expectations in that the location of violence significantly predicts the location of peacekeeping operations, but only after these operations have been in a civil war‐torn country for a considerable length of time. Contrary to our expectations, however, peacekeeping operations do not seem more adept at identifying and responding to government and rebel violence relative to attacks against civilians.